Dark Tourism in Southern Spain (Córdoba): An Analysis of the Demand - Millán, María Genoveva Dancausa (Int J Environ Res Public Health, 2021)
In recent decades, there has been a change in tourists’ tastes; they want to experience something novel. To satisfy this demand, a new type of tourism, known as “dark tourism”, has arisen; it has various modalities, among which cemetery tourism and ghost tourism stand out, in addition to very different motivations from those of the cultural tourist. In this type of tourism, cemeteries are not visited to appreciate their architecture or heritage but to explore a morbid curiosity about the people buried there; ghost tourism or paranormal tourism seizes on the desire to know the events that occurred there and tends to have macabre content. This study analyzes dark tourism in the province of Córdoba in southern Spain with the aim of knowing the profile of the tourist and his motivation. This study additionally will forecast the demand for this type of tourism, using autoregressive integrated moving average (ARIMA) models, which allow us to know this market’s evolution and whether any promotional action should be carried out to promote it.